Pustakawan Melawan Hoax - Deaisya Maryama Alfianne (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2017)
Hoax or fake information has destabilized the Indonesian state security Thus it is necessary to fight hoax librarian's role in various ways. Many cases of false news that raises concerns, noise can even be casualties. Various kinds of issues are always there every second. It's disrupting our lives. The growing issue may gradually change our perspective on things. For example, the problem of terrorism is always associated with Muslims. When in fact terrorizing actions that anyone can do not just Muslims alone. News packed nicely mixed and spiced with elements lies with the intention of attract people to want to read. Most of the media using the hoax is the bait used to make the topics to be warm to be discussed. Literature method used by the author to read the information developed in cyberspace and print media around the issue of a hoax. This paper is expected to motivate the librarians throughout Indonesia to simultaneously fight the hoax in their respective agencies and in the environment in which they live and society. Additionally hope the authors is that the librarian could be a model society not to be provoked by the hoax and the library as a gateway healthy and free hoax information. Action against hoax should we gaungkan at every opportunity.